2019
DOI: 10.1101/609107
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Robust Reconstruction of CRISPR and Tumor Lineage Using Depth Metrics

Abstract: Lineage reconstruction using CRISPR edited barcodes are becoming wide-spread and methods robust against noise are in need. Neighbor-Joining (NJ) algorithm is a robust distance based algorithm extensively used in phylogeny eld. NJ is also used for CRISPR-encoded-lineage (CEL) reconstruction with proper re-rooting since NJ is unrooted algorithm. However, we found NJ works without re-rooting for reconstructing CEL when the lineage contains multiple trees but not for a single tree. Examining why this is the case l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…At the end of the lineage tracing experiment, the indel alleles are collected from individual cells by sequencing and paired with single-cell expression profiles of the cell state (22,23). Then, as in retrospective tracing approaches, computational approaches (29)(30)(31)(32)(33)(34) can reconstruct a phylogenetic tree that best models subclonal cellular relationships (e.g., by maximum-parsimony) from the observed shared or distinguishing alleles. Thus far, Cas9-enabled tracing has been successfully applied to study the cellular progenitor landscape in early mammalian embryogenesis (23,35), hematopoiesis (36), and neural development in zebrafish (22).…”
mentioning
confidence: 99%
“…At the end of the lineage tracing experiment, the indel alleles are collected from individual cells by sequencing and paired with single-cell expression profiles of the cell state (22,23). Then, as in retrospective tracing approaches, computational approaches (29)(30)(31)(32)(33)(34) can reconstruct a phylogenetic tree that best models subclonal cellular relationships (e.g., by maximum-parsimony) from the observed shared or distinguishing alleles. Thus far, Cas9-enabled tracing has been successfully applied to study the cellular progenitor landscape in early mammalian embryogenesis (23,35), hematopoiesis (36), and neural development in zebrafish (22).…”
mentioning
confidence: 99%
“…end while 16: end procedure (We note a similar algorithm has been presented in Sugino et. al [37], although no theoretical guarantees on accuracy are given in that work. )…”
Section: Bottom-up Algorithmmentioning
confidence: 95%
“…Over time, characters may mutate from their unedited states at instantaneous rate λ according to an exponential distribution. While previous models have assumed a per-generation mutation rate [10,37,17], in our model, mutations occur independently from cell division. We believe this is a more accurate representation of current experimental regimes.…”
Section: Problem Setup and Model Assumptionsmentioning
confidence: 99%
“…This does not appear to limit our ability to track 100 serial cell cycles. In fact, we have previously observed that the number of alleles per unit is much less important compared to the rate of editing and the number of coding units [37,38]. A recent study on cell phylogenic analysis has also concluded similarly about the Cas9 base-editor's advantage in having many more targets despite limited edit outcomes [39].…”
Section: Advantages Of Cas9 Base-editorsmentioning
confidence: 99%